1994
DOI: 10.1002/1097-0142(19940515)73:10<2626::aid-cncr2820731026>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Malignant melanoma of the vulva treated by radical hemivulvectomy. A prospective study of the gynecologic oncology group

Abstract: Background. Beginning in 1983, the Gynecologic Oncology Group (GOG) conducted a prospective clinicopathologic study of primary malignant melanoma of the vulva. The objectives of this study were to determine the relationship of histopathologic parameters and microstaging to the International Federation of Gynaecology and Obstetrics (FIGO) staging and prognosis. Methods. All patients with primary untreated malignant melanoma of the vulva and no history of previous or subsequent other primary invasive malignancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
3
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(87 citation statements)
references
References 15 publications
1
78
3
5
Order By: Relevance
“…Furthermore, there is no evidence that vulvar melanoma behaves any differently than does cutaneous malignant melanoma. 21,22 Most surgeons have, like us, abandoned radical vulvectomy as the treatment of choice because it is difficult to accept the high complication rate and resulting deformity (which may cause sexual problems and somatopsychic reactions) associated with radical surgery when there is no clear evidence that it provides any improvement in survival.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is no evidence that vulvar melanoma behaves any differently than does cutaneous malignant melanoma. 21,22 Most surgeons have, like us, abandoned radical vulvectomy as the treatment of choice because it is difficult to accept the high complication rate and resulting deformity (which may cause sexual problems and somatopsychic reactions) associated with radical surgery when there is no clear evidence that it provides any improvement in survival.…”
Section: Discussionmentioning
confidence: 99%
“…5 The biological behavior of primary vulvar and extragenital cutaneous malignant melanoma appeared to be comparable. 13,16 However, some studies 1,3,20 have shown that the overall prognosis for patients with vulvar melanoma is generally poor, compared with cases of cutaneous melanoma and invasive vulvar carcinoma, with a higher tendency towards regional and distant recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, over the last few years, there have been some reports suggesting that acceptable survival has been achieved through less radical procedures performed on early disease. [6][7][8][9][10][11][12][13][14] In the literature, it is suggested that the clinical and postoperative staging is the most significant predictor of survival. Depth of invasion and presence of ulceration 13,[15][16][17] are the most important histopathological prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Vulvar melanoma is staged according to AJCC TNM classification for cutaneous melanoma [33]. No staging system has demonstrated prognostic accuracy for vaginal melanoma.…”
Section: Stagingmentioning
confidence: 99%